Management consulting labs-Galp loyalty - Paiva, Diogo Fernando Almeida (2012)
The objective of this consulting project was to assist Galp Energia in its approach to loyalty. In order to do so, two hypotheses were defined. The first assumed there was value to capture in the existing approach. The second held that it was possible to create value through a radically innovative approach. The methodology used to corroborate those hypotheses encompassed several quantitative analyses, as well as desk research and market research. As a result, a compilation of recommendations comprising implementation proposals that considered both hypotheses as valid was presented in order to suggest a paradigm change